STUDI KEANEKARAGAMAN MAKROZOOBENTOS DI SUNGAI MUARA KECAMATAN MUARA KABUPATEN TAPANULI UTARA PROVINSI SUMATERA UTARA - Sanjay M. Ompusunggu; Mardame Pangihutan Sinaga; Daniel Tony Edyt Siburian (Journal of Research and Publication Innovation, 2025)
The Muara River is a river in Muara District, North Tapanuli Regency. In the river there are various types of macrozoobenthos which have a big influence on the ecosystem in the river. The aim is to determine the diversity of macrozoobenthos and the dominant types of macrozoobenthos in the Muara River, Muara District, North Tapanuli Regency. The type of macrozoobenthos found in the Muara River is the Gastropoda class with 2 species, namely Pillaampullacea and Red-rimmed with a total of 59 individuals. The Bivalvia class consist of 1 species, namely Polymesodaerosa with a total of 25 individuals, so the total found was 84 individuals. The diversity value (H’) in the Muara River is 1,07 in the medium category. The uniformity value (E) of 0,97 is included in the stable category. The dominance index (C) value is 0,35, which is low. The Macrozoobenthos that dominates in the Muara River is the Gastropoda class at 70%, while the Bivalvia class is at 30%.